Peran Komunikasi Budaya dalam Keberhasilan Program Rumah Pilah Sampah di Kelurahan Sungai Baru: Penelitian - Nina Delwina; M. Agus Humaidi; Lieta Dwi Novianti; Amelia Puspita (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to understand how culturally-based communication contributes to the success of the program and to identify obstacles that arise in its implementation. Using a qualitative approach and case study method in Sungai Baru Village, data were obtained through in-depth interviews, field observations, and documentation with eight key informants. The results show that communication that prioritizes local values ​​such as deliberation (bapakat), mutual cooperation (basa banua), and the use of familiar and polite regional languages ​​can build closeness and increase community involvement. The process of disseminating information about the program follows five stages of innovation diffusion: knowledge, persuasion, decision, implementation, and confirmation, strengthened by the role of community leaders, social networks, and local communication media. However, this program is not without challenges, such as low awareness of the program's benefits, differences in communication styles between parties, social awkwardness, and limited supporting facilities. This study concludes that communication that aligns with community cultural values ​​is key to the success of implementing an environment-based program oriented towards community participation.